Children’s Human Rights Education in Swiss Curricula An Intercultural Perspective into Educational Concepts - Rinaldi, Stefanie; Moody, Zoe; Darbellay, Frédéric (Swiss Journal of Educational Research, 2020)
Over the last few years, Switzerland has introduced three new curricula for primary and lower-secondary schools, one for each linguistic region. On several occasions, Switzerland has claimed that these curricula meet the required standards of children’s human rights education as conceptualized in international documents such as the United Nations Convention on the Rights of the Child or the United Nations Declaration on Human Rights Education and Training. The aim of this article is twofold: first, to provide a conceptual study of the theoretical frameworks related to children’s human rights education and other close related educational forms; second, to analyse how these different concepts are translated and implemented through the three regional curricula.